A pilot study: a possible implication of Candida as an etiologically endogenous pathogen for oral lichen planus - Hong He; Xinyu Xia; Haiping Yang; Qiao Peng; Jiaoer Zheng (BMC, 2020)
Abstract Background The aim of this study was to investigate the prevalence and genotypic profiles of Candida albicans in patients with oral lichen planus (OLP). Materials and methods Positive rates and genotypic profiles of Candida albicans strains from OLP patients and healthy controls were analyzed. Random amplified polymorphic DNA and internal transcribed spacer of ribosome DNA polymerase chain reactions were used to sequence the DNA of these strains, and then their genetic similarity was measured using BLAST, UIV Band, and Vector NTI Suite Sequence Analyses Software. Results The prevalence of C. albicans strains detected from erosive-OLP, non-erosive OLP, and normal individuals was 18.87, 18.75, and 7.92%, respectively. Four different genotypes were revealed by the two methods. To be specific, type I was found only in the healthy subjects; type II a and II b were found in non-erosive OLP, and type III was identified in erosive OLP. Intragroup similarity coefficients, i.e. SAB were 100%, and inter-groups similarity coefficients, i.e. SAB were less than 30%. Conclusions The genotypic results of C. albicans in OLP revealed an endogenous rather than exogenous infection of C. albicans. In addition, a possible pathogenic role of C. albicans in OLP, with the etiologic sense contributing to a more proper recognition on the pathogenesis, development, and progression of OLP, as well as some strategies for its diagnosis and treatment were identified.